IMPLEMENTASI PENDIDIKAN PROFETIK DI MADRASAH TSANAWIYAH (STUDI KASUS DI MTS AN-NUUR BULULAWANG) - Dian Mohammad Hakim (VICRATINA, 2017)
In order to build the character of students, needed a model of education. One of the model of education is prophetical education. Prophetical education insisted three values based on the Qur’an; humanization, liberation and trancedention to the teaching and learning process. The research tried to recognize how to implemented prophetical education in the Islamic junior high school of An-Nuur Bululawang. Data is gained through depth interviews and participant observation. The result of the studies showed that to implemented prophetical education could be done by modelling or exemplary (uswah hasanah), explaining and clarifying to students continuously about bad value and good value and character –based education  Keyword: Implementation, prophetical education